2021
DOI: 10.3390/ijms23010433
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory, Antioxidant, Moisturizing, and Antimelanogenesis Effects of Quercetin 3-O-β-D-Glucuronide in Human Keratinocytes and Melanoma Cells via Activation of NF-κB and AP-1 Pathways

Abstract: Quercetin 3-O-β-D-glucuronide (Q-3-G), the glucuronide conjugate of quercetin, has been reported as having anti-inflammatory properties in the lipopolysaccharide-stimulated macrophages, as well as anticancer and antioxidant properties. Unlike quercetin, which has been extensively described to possess a wide range of pharmacological activities including skin protective effects, the pharmacological benefits and mechanisms Q-3-G in the skin remained to be elucidated. This study focused on characterizing the skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 91 publications
0
22
0
Order By: Relevance
“…In periodontally healthy conditions, ROS contribute to the oxidative killing of pathogens, while, during periodontitis, the homeostatic imbalance between ROS and antioxidant defense systems acts as intracellular signal transducers that promote cell death and cause tissue damage. Several studies have demonstrated the capability of QUE to reduce either in vitro and in vivo oxidative stress and inflammation [ 47 , 48 , 49 , 50 , 51 ]. In particular, the antioxidant effects of QUE seem to be related to the presence in a heterocyclic ring of a catechol group (a 2,3-double bond at position 3 and a hydroxyl substitution at position 5) [ 50 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In periodontally healthy conditions, ROS contribute to the oxidative killing of pathogens, while, during periodontitis, the homeostatic imbalance between ROS and antioxidant defense systems acts as intracellular signal transducers that promote cell death and cause tissue damage. Several studies have demonstrated the capability of QUE to reduce either in vitro and in vivo oxidative stress and inflammation [ 47 , 48 , 49 , 50 , 51 ]. In particular, the antioxidant effects of QUE seem to be related to the presence in a heterocyclic ring of a catechol group (a 2,3-double bond at position 3 and a hydroxyl substitution at position 5) [ 50 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…The significant improvement in the barrier function (trans-epidermal water loss values decreased by 21% and 27% versus baseline at 1 and 2 months, respectively) and EASI score (decreased by 39% and 49%) confirmed the relevance of our model to evaluate ingredients that can be used to improve atopic-prone skin. The activity of the Castanea sativa extract may be explained by its flavonoid profile, particularly flavonoid glucosides, and among them, the major compounds miquelianin (Quercetin-3-O-glucuronide) and astragalin (Kampferol 3-O- glucuronide), as these two compounds are known as NF kB pathway modulators [ 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in an in vitro study, the aglycone form of hesperidin is efficiently taken up by skin fibroblasts, but does not protect them against UVA-induced damage, while hesperetin-7-glucuronide could not be detected in skin fibroblasts as an aglycone, but it is protective against UVA radiation [ 58 ]. In contrast, quercetin and its major metabolites, quercetin-3-glucuronide, exhibited a cytoprotective activity on UVB-induced keratinocyte cell damage [ 59 ]. Therefore, the biotransformation and active metabolites of quercitrin and hyperoside in keratinocytes need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%